Training and Implementation of an SMS Gateway For Village Information and Announcements in The Indonesia–Timor Leste Border Region - Emerensiana Ngaga; Yovinia Carmeneja Hoar Siki; Donatus J Manehat; Emanuel Jando; Jacob Soares; Haryanto Santoso (International Journal Of Community Service, 2026)
Napan Village, located in the RI–RDTL border area, faces communication challenges due to limited internet access and the community’s reliance on basic mobile phones. This condition slows down the dissemination of village information, which is still carried out manually. This community service program aims to provide a practical solution through the implementation of an SMS Gateway system using Gammu and MySQL. Village officials received outreach and training on system installation, resident database management, and mass message delivery. Evaluation results showed a positive response: 92% of participants found the training easy to follow, 88% experienced the benefits of faster information delivery, and 90% stated that the application was easy to use. The implementation of the SMS Gateway has proven to enhance communication efficiency and strengthen the digital capacity of village officials. The program is expected to be further developed by integrating the system with other administrative services to ensure its long-term sustainability.